Fluctuations and growth in a near full employment economy : a quarterly econometric analysis of the Netherlands - Driehuis, W. (Rotterdam : Rotterdam University Press, 1972)
This book is about the construction and application of a completely econometric model for the Netherlands.
Includes index.
Includes bibliographical references: p. 258-266.
oo 07/09/2018
Loans
Keywords: Macroeconomics; Netherlands